The Nature of Non-verbal Communication Skills Practiced by Educational Counselors in Individual Guidance (Journal Of Educational and Psychological Researches, 2022)
This research is an attempt to achieve the following objectives: 1. identifying the nature of the non-verbal communication skills practiced by educational counselors in individual guidance. 2. Identifying the significant differences between non-verbal communication skills exercised by educational counselors from their point of view in regard to their gender (male-female). The researcher used a questionnaire as a tool prepared based on exploratory questions of educational counselors and literature. It has consisted of (26) items over four domains applied to a sample of (50) educational counselors (male and female) who have been chosen randomly from schools located in Baghdad Education Directorate Rusafa / 2. It was treated statistically using the statistical program (SPSS). The results of the current research showed that the nature of the non-verbal communication skills practiced by educational counselors in individual guidance from their point of view was moderate. There are no statistically significant differences at the Level of indication (0, 05) in the nature of non-verbal communication skills between males and females.